Pretend Play as a Key to Enhancing Sexuality Knowledge in Children with Mild Intellectual Disability - Alucyana, Alucyana; Ikhwanisifa, Ikhwanisifa; Siregar, Juliarni; Zeni, Sisra; Nabila, Restu (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This study aims to analyze the effect of the pretend play method on sexuality knowledge in children with mild intellectual disabilities, while controlling for age, concentration, and verbal ability in special needs schools. This quantitative research uses an experimental approach with a pretest-posttest control group design. A total of 60 children, aged 11–14 years, with mild intellectual disabilities were selected through stratified random sampling and assigned to either the experimental group or the control group, each consisting of 30 participants. Data collection was conducted using modules and tests. The results revealed that the pretend play method significantly improved sexuality knowledge in children with mild intellectual disability, with an F value for the pretend play variable of 540.1 and a significance level of p=0.00 (p<0.01). Additionally, age, concentration, and verbal ability were positively correlated with sexuality knowledge, confirming their importance as covariates. These findings suggest that the pretend play method can serve as an effective educational strategy for enhancing sexuality knowledge among children with mild intellectual disability, highlighting the importance of integrating structured play-based learning into special education curricula to support their cognitive and social development.